NATIONAL IDENTITY AND THE SUSTAINABILITY OF STATE - K. А. Kuznetsov; P. А. Tschelin (Сравнительная политика)
The authors of this article offer a different view on the conditions and principles of successful state development. In this article the concept of national identity is regarded as the key criterion of the analysis of the state development. The authors elaborate a new definition of the concept of national identity and present the main provisions of the theory of state sustainability.